Analisi Product Innovation dan Store Atmosphere terhadap Purchase Intention UMKM Kuliner Kota Sukabumi - Mariati Tirta Wiyata; Zeffanya Raphael Wijaya; Bambang Somantri (Transpublika Publisher, 2025)
The study seeks to analyze the problem of sales revenue that tends to stagnate in the culinary MSME shop at the former Sukabumi City Terminal. The results of observations in the field show that there is an influence of product innovation and store atmosphere on consumer purchase intention. In general, consumers think about culinary usually product innovation becomes an attraction. In addition, consumers generally assess shops or stores on the first impression is from the store atmosphere that is felt in the form of table layouts, chairs, display cases, room colors, and others. Quantitative research analysis using the SPSS application. Taking respondents from the population through random sampling which amounted to 97 (ninety seven) people. Analyze the quality of the instrument by means of validity tests and reliability tests. Furthermore, the data quality is tested with the classical assumption test, then for hypothesis testing using multiple regression calculations, t tests, F tests, and determination coefficient tests. The results can be concluded that product innovation and store atmosphere can increase intention. So that it can increase revenue and profits for MSME shop owners.